Les voyages d’Élisabeth II, des visites très sélectives dans un empire déclinant - Claire Weishar; Marie-Françoise Fleury; Fulano de Thal (Confins)
The article puts Elizabeth II's travels into perspective, in a world of declining British influence. The trend is clear: apart from trips to European countries (notably France and Germany), the most trips were made to countries where the Queen was sovereign until the end, notably Canada (22 trips) and Australia (15 trips) and the Caribbean and Pacific islands that remained under British sovereignty. Then, in descending order, to Commonwealth countries, with a preference for those where she remained Sovereign